(untitled) (The Educator Journal, 2022)
This research was conducted to determine the efficiency of biogas generation from kitchen garbage and to present the various biogas production processes. The anaerobic digestion of kitchen waste produces a valuable energy resource, and the activity-based laboratory approach was applied for this purpose. The anaerobic breakdown is a microbiological process that produces biogas, mainly composed of methane and carbon dioxide. Biogas can be utilized as a source of energy and for a variety of other purposes. On the other hand, any potential applications require knowledge and information on the composition and quantity of components in the biogas produced. Sodium hydroxide must be added to maintain alkalinity and pH in the digester. The cow dung slurry, as well as kitchen garbage, were added to this reactor. This mixed Inoculum was combined to produce biogas in a small-scale activity. The production of biogas and methane from starch-rich and sugary material is determined on a small scale using simple digesters.